QUANTIFICATION OF THROMBUS BURDEN AS AN INDEPENDENT PREDICTOR OF INTRA-PROCEDURAL NO-REFLOW IN PATIENTS WITH ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION UNDERGOING PRIMARY PERCUTANEOUS CORONARY REVASCULARIZATION - Kumar, Rajesh; Khan, Kamran Ahmed; Shah, Jehangir Ali; Ammar, Ali; Kumar, Dileep; Khowaja, Sanam; Sial, Jawaid Akbar; Kazmi, Samra; Murtaza, Muhammad; Karim, Musa (Journal of Ayub Medical College Abbottabad, 2022)
Background: Aim of this study was to perform quantitative evaluation of high thrombus burden (Grade ‰¥4) as an independent predictor of slow/no reflow phenomenon during primary percutaneous coronary interventions (PCI) of patients with ST-segment elevation myocardial infarction (STEMI). Methods: In this analytical cross-sectional study we included consecutive patients who have undergone primary PCI for STEMI at a tertiary care cardiac center of the Pakistan. High thrombus burden was defined as angiographic thrombus grade ‰¥ 4. The thrombolysis in myocardial infarction (TIMI) flow rate < III was defined as slow/no reflow phenomenon. Results of multivariate logistic regression analysis for slow/no reflow phenomenon were reported as odds ratio (OR). Results: This analysis included 747 patients, 78.2% (584) patients were male and mean age was 55.82±11.54 years. High thrombus burden was observed in 68.1% (509) of the patients. Slow/no reflow phenomenon was observed in 33.6% (251) which was more common among patients in high thrombus burden group, 39.7% (202/509) vs. 20.6% (49/238); p<0.001. Adjusted OR of thrombus Grade ‰¥ 4 was 2.33 [1.6 -3.39]; p<0.001. Other significant variables were female gender (1.51 [1.01 -2.27]; p=0.045), left ventricular end-diastolic pressure (LVEDP) ‰¥20 mmHg (2.34 [1.69 -3.26]; p<0.001), total lesion length ‰¥ 20 cm (1.54 [1.09-2.16]; p=0.014), and neutrophil count ‰¥ 8.8 cells/µL (1.72 [1.22 -2.43]; p=0.002). Conclusion: High thrombus burden (Grade ‰¥ 4) is a significant and an independent predictor of the slow/no reflow phenomenon. While predicting slow/no reflow phenomenon, thrombus burden should be given due importance along with other significant factors such as gender, LVEDP, lesion length, and neutrophil counts.